2009
DOI: 10.4271/2009-01-2693
|View full text |Cite
|
Sign up to set email alerts
|

Emissions with Heavy-duty Diesel Engines and Vehicles using FAME, HVO and GTL Fuels with and without DOC+POC Aftertreatment

Abstract: This study presents emission results measured with renewable and synthetic diesel fuels. Three engines and five city buses were studied. The efficiency of diesel oxidation catalyst combined to particle oxidation catalyst (POC®) was measured with two engines. The studied diesel fuels were EN590, FAME, HVO and GTL. In most cases all regulated emissions decreased with HVO and GTL fuels compared to conventional EN590 diesel fuel. With FAME, the NO x emissions were higher compared to EN590, but other emissions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 22 publications
6
49
1
2
Order By: Relevance
“…Briefly, decreased PM 0.5 and BC concentrations were not seen during the 3-day experiment with NEXBTL as could have been expected on the basis of laboratory tests comparing NEXBTL and EN590 in heavy vehicle engines (Murtonen et al 2010). A major reason for this was probably that the trucks, having the best control of engine emissions with both fuels (EURO 5, all equipped with particle filter), had also the highest activities and largest fuel consumption during the test periods.…”
Section: Sources Of Sub-micrometer Particlesmentioning
confidence: 91%
See 2 more Smart Citations
“…Briefly, decreased PM 0.5 and BC concentrations were not seen during the 3-day experiment with NEXBTL as could have been expected on the basis of laboratory tests comparing NEXBTL and EN590 in heavy vehicle engines (Murtonen et al 2010). A major reason for this was probably that the trucks, having the best control of engine emissions with both fuels (EURO 5, all equipped with particle filter), had also the highest activities and largest fuel consumption during the test periods.…”
Section: Sources Of Sub-micrometer Particlesmentioning
confidence: 91%
“…Besides efficient ventilation, that should be mandatory in all enclosed spaces with emissions, it is important to decrease the emissions through better engine technologies, higher fuel quality, and advanced after-treatment techniques. However, it should be noted that the introduction of novel engine and exhaust after-treatment technologies into vehicles used in underground mines may change not only the quantity but also the physico-chemical characteristics and toxic properties of emissions (Murtonen et al 2010;Jalava et al 2012). In this study, a 3 day experiment was conducted when fossil diesel fuel was changed to 100% renewable diesel fuel in all the vehicles in the underground mine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The engine was tuned and the NO x emission was reduced. Murtonen et al [9] used EN590 diesel fuel, FAME, HVO, and GLT fuels in the diesel engine and the results showed that NO x emission was high in FAME when compared with HVO and GTL. The other emissions were reduced compared with EN590 diesel fuel.…”
Section: Introductionmentioning
confidence: 97%
“…The urge to lower CO 2 emissions and to reduce fossil oil dependence has increased the use of biobased alternative fuels. New HVOs (paraffinic hydrotreated vegetable oils; e.g., NExBTL by Neste Oil) and synthetic F-T (Fischer-Tropsch) diesel fuels (e.g., GTL [gas-to-liquid] by Shell), which have very similar properties, are reported to lower the regulated as well as the unregulated engine exhaust emissions compared with regular diesel fuel (e.g., Tilli et al, 2010;Abu-Jrai et al, 2009;Heikkilä et al, 2009b;Knothe et al, 2010;Murtonen et al, 2010;Aatola et al, 2008). The absence of polyaromatic hydrocarbons (PAHs), the higher cetane number, and the lower distillation endpoint of HVO fuel compared with conventional EN590 (sulfur content <10 ppm) fuel are usually proposed as the main characteristics for lower NO x and PM emissions (Gill et al, 2011;Nylund et al, 2011).…”
Section: Introductionmentioning
confidence: 99%